Excimer formation and dual fluorescence emission of a hydroxyquinoline based macrocyclic tripod: existence of intra and intermolecular π-stacking. Issue 109 (15th November 2016) - Rohini,; Baral, Minati; Kanungo, B. K.
Abstract : The excited state reaction of 1, 4, 7-tris-(5-methylene-8-hydroxyquinoline)-1, 4, 7-triazacyclononane was studied in solution. The intramolecular-π-stacked tripod shows pH-dependent eximer emission and dual fluorescence due to intermolecular π-stacking. Abstract : The excited state reaction of a conformationally flexible molecule, 1, 4, 7-tris-(5-methylene-8-hydroxyquinoline)-1, 4, 7-triazacyclononane, (9N3Me5Ox), was studied in solution. The unique geometry of this compound forces the two 8-hydroxyquinoline (8HQ) rings to undergo a face to face π–π stacking in the ground state, while the third ring forms a T-shaped orientation with face to edge interaction. The existence of intramolecular π-stacking interaction of the 8HQ units was established by 1 H NMR and luminescence spectroscopy. Due to intramolecular π-stacking, chemical shifts of the 8HQ protons in neutral form were slightly shielded in the NMR spectrum. In neutral solution, excimer emission was observed with appearance of an additional strong red shifted band in the fluorescence spectra at moderate concentration due to intermolecular π-stacking interaction among the 8HQ units in the excited state. The dual emission of the neutral solution of the molecule vanished with change in pH or concentration of the solution. At very low concentration, very high concentration, as well as in low pH or high pH, only one emission band was observed. Time-resolved fluorescence data supported the nonexistence of excited state intramolecular proton transfer (ESIPT) or excited state phototautomerization. The studies of fluorescence spectra of the compound in protic, aprotic and polar protic solvent confirmed the assistance of protic solvent in formation of intermolecular π-stacking excimer. The lifetime of the tripod containing three 8HQ has been enhanced to nano-second level causing a "turn on" of fluorescence as compared to the earlier reported unsubstituted short-lived 8HQ which has life time picoseconds.